2017
DOI: 10.1371/journal.pone.0183015
|View full text |Cite
|
Sign up to set email alerts
|

Sources of implicit and explicit intergroup race bias among African-American children and young adults

Abstract: Implicit intergroup bias emerges early in development, are typically pro-ingroup, and remain stable across the lifespan. Such findings have been interpreted in terms of an automatic ingroup bias similar to what is observed with minimal groups paradigms. These studies are typically conducted with groups of high cultural standing (e.g., Caucasians in North America and Europe). Research conducted among culturally lower status groups (e.g., African-Americans, Latino-Americans) reveals a notable absence of an impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…Importantly, previous research reported not only positive, but also non-significant or even negative effects of exposure (Verkuyten and Kinket, 2000;Nowicki and Sandieson, 2002;Smith-D'Arezzo and Moore-Thomas, 2010;Kurtz-Costes et al, 2011;Vittrup and Holden, 2011;Pahlke et al, 2012;Vezzali et al, 2012;Huckstadt and Shutts, 2014;Aboud et al, 2015;Gibson et al, 2017;Ersan et al, 2020). Placement of children with disabilities in a general classroom does not automatically produce peer acceptance and social inclusion (Kluwin and Gonsher, 1994;McEvoy and Odom, 1996).…”
Section: Exposurementioning
confidence: 98%
“…Importantly, previous research reported not only positive, but also non-significant or even negative effects of exposure (Verkuyten and Kinket, 2000;Nowicki and Sandieson, 2002;Smith-D'Arezzo and Moore-Thomas, 2010;Kurtz-Costes et al, 2011;Vittrup and Holden, 2011;Pahlke et al, 2012;Vezzali et al, 2012;Huckstadt and Shutts, 2014;Aboud et al, 2015;Gibson et al, 2017;Ersan et al, 2020). Placement of children with disabilities in a general classroom does not automatically produce peer acceptance and social inclusion (Kluwin and Gonsher, 1994;McEvoy and Odom, 1996).…”
Section: Exposurementioning
confidence: 98%
“…Few mothers reported explicitly speaking to their children about race or interracial interactions in early childhood; moreover, the frequency of such conversations was unrelated to children's racial biases in the one study investigating this relation in a White U.S. sample (Pahlke, Bigler, & Suizzo, ). Studies focused on the intergroup messages provided by Black U.S. parents indicate that education on issues of civil rights, Black history, and racial discrimination are associated with decreased explicit pro‐White bias (Gibson, Rochat, Tone, & Baron, ; Spencer, ) . However, in the one study to examine implicit biases, these types of intergroup messages were associated with increased implicit pro‐White bias among Black children, but only among those attending racially homogeneous schools (Gibson et al., ).…”
Section: Parental Socializationmentioning
confidence: 99%
“…Studies focused on the intergroup messages provided by Black U.S. parents indicate that education on issues of civil rights, Black history, and racial discrimination are associated with decreased explicit pro‐White bias (Gibson, Rochat, Tone, & Baron, ; Spencer, ) . However, in the one study to examine implicit biases, these types of intergroup messages were associated with increased implicit pro‐White bias among Black children, but only among those attending racially homogeneous schools (Gibson et al., ).…”
Section: Parental Socializationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also recent evidence from North America indicating that positive cultural messaging can increase ingroup racial positivity for members of culturally marginalized racial groups. For example, one recent study conducted in the United States found that Black young adults who attend Historically Black Colleges, where Black racial identity is celebrated and positively reinforced, have stronger levels of implicit pro-Black/anti-White racial bias on an IAT than those who do not attend these colleges (Gibson, Rochat, Tone, & Baron, 2017).…”
Section: Early Implicit Racial Bias Change 16mentioning
confidence: 99%